Optimal Loyalty‐Based Management. Issue 2 (14th December 2016) - Shin, Dongsoo
Abstract : We study an agency model in which an entrepreneur selects a manager from a candidate set. The selected manager's effort improves the project's potential environment, and is a hidden action. The realized project environment is the entrepreneur's private information. A manager's utility has two components—(i) loyalty, with which the manager values the organization's profit, and (ii) selfishness, with which the manager values the monetary transfer he receives from the entrepreneur. We find that if the manager's task is easy enough, it is optimal to use a purely loyal manager. Otherwise, it can be optimal to use a manager with mixture of loyalty and selfishness—the manager's mixed motivation alleviates the entrepreneur's misrepresenting incentive, and as a result, the output distortion in the optimal contract can be reduced. In addition, when it is optimal to use a manager with mixed motivations, the entrepreneur selects someone who is more selfish than loyal.